"Exon" as an agent of rehabilitation for patients with viral infections - a brief review - Martynov, Artur; Lukianenko, Timur (Annals of Mechnikov’s Institute, 2022)
Exon is a composition of acidic peptides capable of self-organization and self-adaptation in the body, the mechanism of which is based on the blockade the nuclear import/export peptides and prevent crossing the nuclear membrane with virion fragments. The Exon selectively binds to importin’s signal peptides through molecular recognition and prevents the nuclear pore recognizing and opening for viral components. In fact, 90% of all viruses use the cell nucleus for increase the speed of their own replication. Adaptation to the drug is impossible on part of the virus and the human body due to the fact that it is a quasi-living system capable of self-organization and its composite pharmacophore adapts itself for each person and virus. The minimum effective concentration (MEC) of Exon against the influenza virus, which completely inhibits the synthesis of the virus, is 0.05 mg/mL. Effectiveness of Exon has a dose-dependent character. Also, Exon has a direct antiviral effect against the influenza virus (H3N2 and H1N1 srrains) and coronavirus. Exon also has a virustatic (inhibiting) and virulicidal (inactivating) effect on TGS and bovine diarrhea viruses. On basis of Exon it is possible to create chemical preparations for the treatment and prevention of infectious diseases of viral etiology in human. The chemotherapeutic index for rabbits with keratoconjunctivitis/encephalitis caused by HSV1 when using Exon was 1000, which indicates the promise of Exon as a highly effective antiviral substance with a broad action spectrum and low toxicity in the complex of rehabilitation measures for herpetic lesions. According to the results of the Exon use in the complex rehabilitation of patients with COVID-19, the patients recovery time is statistically significantly reduced according to two criteria: the time of disappearance of the viral antigen/RNA and the time of Rx - normalization in the presence of pneumonia.